2022
DOI: 10.1002/pro.4471
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Escherichia coli pyridoxal 5′‐phosphate homeostasis protein (YggS): Role of lysine residues in PLP binding and protein stability

Abstract: The pyridoxal 5′‐phosphate (PLP) homeostasis protein (PLPHP) is a ubiquitous member of the COG0325 family with apparently no catalytic activity. Although the actual cellular role of this protein is unknown, it has been observed that mutations of the PLPHP encoding gene affect the activity of PLP‐dependent enzymes, B6 vitamers and amino acid levels. Here we report a detailed characterization of the Escherichia coli ortholog of PLPHP (YggS) with respect to its PLP binding and transfer properties, stability, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Thus, both of the Arabidopsis PLPHPs have the capacity to bind PLP. They behave as monomers with PLP likely solvent exposed similar to the reported oligomeric state of bacterial and yeast homologs (Eswaramoorthy et al, 2003;Prunetti et al, 2016;Tremiño et al, 2017;Tramonti et al, 2022), although the human ortholog is reported to exist as both monomers and dimers in vitro (Tremiño et al, 2018;Fux and Sieber, 2020). Significantly, the monomeric state of Arabidopsis PLPHPs contrasts with reported PLP-dependent enzymes from all kingdoms, all of which have higher oligomeric states (Eliot and Kirsch, 2004).…”
Section: Both Plphp Homologs From Arabidopsis Bind Plp In a Schiff-ba...supporting
confidence: 57%
See 3 more Smart Citations
“…Thus, both of the Arabidopsis PLPHPs have the capacity to bind PLP. They behave as monomers with PLP likely solvent exposed similar to the reported oligomeric state of bacterial and yeast homologs (Eswaramoorthy et al, 2003;Prunetti et al, 2016;Tremiño et al, 2017;Tramonti et al, 2022), although the human ortholog is reported to exist as both monomers and dimers in vitro (Tremiño et al, 2018;Fux and Sieber, 2020). Significantly, the monomeric state of Arabidopsis PLPHPs contrasts with reported PLP-dependent enzymes from all kingdoms, all of which have higher oligomeric states (Eliot and Kirsch, 2004).…”
Section: Both Plphp Homologs From Arabidopsis Bind Plp In a Schiff-ba...supporting
confidence: 57%
“…Expression and purification of the AtPLPHP1 K55A mutant followed by spectral analysis indicated an at least 10-fold lower amount of bound PLP, thus supporting the involvement of K55 in Schiff’s base formation with the coenzyme (Figure 2B). Although, it should be noted that a second lysine not involved in Schiff’s base formation with PLP but required for functionality as demonstrated with the E. coli homolog (Tramonti et al, 2022) is conserved in the Arabidopsis orthologs (Figure 2A).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, the phenotypic features described here for PipY ox cultures should help studies on the structure–function relationship at PipY/PLPBP or concerning the regulatory complexities of accumulation of giant polyP granules in S. elongatus . For instances, PipY ox derivatives carrying mutations at functionally relevant or conserved residues ( Tramonti et al, 2022 ; Tremiño et al, 2022 ) can be easily compared in the presence of IPTG and further analyzed for traits of interest.…”
Section: Resultsmentioning
confidence: 99%